Improving Assessments of Connection to Nature: A Participatory Approach - Salazar, Gabby; Monroe, Martha C.; Jordan, Catherine; Ardoin, Nicole M.; Beery, Thomas H. (Frontiers in Ecology and Evolution, 2021)
Experiences in nature benefit humans in a variety of ways, including increasing health and wellbeing, reducing stress, inspiring creativity, enhancing learning, and fostering environmental stewardship values. These experiences help define the relationship people have with nature which is often correlated with a person’s level of environmental concern as well as their engagement in pro-environmental behaviors. A more informed understanding of the ways in which interactions with the natural environment can foster connection to nature requires that we are able to measure our perceived relationship to the environment. Dozens of tools measure people’s connection to nature—the strength of those perceived relationships with the natural world. Although the tools have been primarily developed to answer research questions, practitioners are increasingly interested in understanding whether and in what ways their work—in areas including environmental education, urban planning, and park management, for example—influence people’s connection to nature. In 2018, we launched a participatory process involving researchers and practitioners in a review of existing connection to nature assessment tools with the intention of identifying tools that would be useful to practitioners, as well as defining needs in research. This paper chronicles the process’s outcomes, including a discussion of opportunities for future research.